Environmental Persistence of the World's Most Burdensome Infectious and Parasitic Diseases - Hopkins, Skylar R.; Jones, Isabel J.; Buck, Julia C.; LeBoa, Christopher; Kwong, Laura H.; Jacobsen, Kim; Rickards, Chloe; Lund, Andrea J.; Nova, Nicole; MacDonald, Andrew J.; Lambert-Peck, Miles; De Leo, Giulio A.; et al. (Frontiers in Public Health, 2022)
Humans live in complex socio-ecological systems where we interact with parasites and pathogens that spend time in abiotic and biotic environmental reservoirs (e.g., water, air, soil, other vertebrate hosts, vectors, intermediate hosts). Through a synthesis of published literature, we reviewed the life cycles and environmental persistence of 150 parasites and pathogens tracked by the World Health Organization’s Global Burden of Disease study. We used those data to derive the time spent in each component of a pathogen’s life cycle, including total time spent in humans versus all environmental stages. We found that nearly all infectious organisms were “environmentally mediated” to some degree, meaning that they spend time in reservoirs and can be transmitted from those reservoirs to human hosts. Correspondingly, many infectious diseases were primarily controlled through environmental interventions (e.g., vector control, water sanitation), whereas few (14%) were primarily controlled by integrated methods (i.e., combining medical and environmental interventions). Data on critical life history attributes for most of the 150 parasites and pathogens were difficult to find and often uncertain, potentially hampering efforts to predict disease dynamics and model interactions between life cycle time scales and infection control strategies. We hope that this synthetic review and associated database serve as a resource for understanding both common patterns among parasites and pathogens and important variability and uncertainty regarding particular infectious diseases. These insights can be used to improve systems-based approaches for controlling environmentally mediated diseases of humans in an era where the environment is rapidly changing.